The Struggle for Saratov Theological Seminary in the Context of Church-State Relations in 1944–1951 - Grigory V. Bartenev (Вестник Екатеринбургской духовной семинарии, 2024)
The article highlights the study of the process of overcoming the resistance of the USSR party and economic leadership of the regional level to the opening and functioning of religious educational institutions in the post-war period, using an example of the revival of the Saratov Theological Seminary in 1944–1951. The framework of the period under study is determined by the date of adoption of the Resolution of the Council of People’s Commissars of the USSR on the opening of theological and pastoral courses in Saratov in 1944 and the first graduation of the seminary in 1951. This period is divided into three parts: a long process of resistance by the Saratov authorities to the opening of the seminary and failure to provide premises for it (1944–1947); a relatively calm period of functioning of the seminary; and a period of reaction of local authorities to the Epiphany celebration in 1949, known as the “Saratov Font”, which led to a severe two-year crisis in church-state relations in Saratov and an attempt to close the seminary. The article shows the role of the bishops who ruled the Saratov diocese and were responsible for the revival of the Saratov seminary: Archbishops Gregory (Chukov) and Alexy (Palitsyn), Bishops Paisy (Obraztsov) and Boris (Vik), as well as the assistance of Archbishop Philip (Stavitsky) in overcoming the difficulties that arose, and support from the Patriarchs of the Russian Orthodox Church Sergius (Stragorodsky) and Alexy (Simansky). These events are considered in connection with the processes of deterioration of church-state relations in the USSR, which began in 1946 after the change of leaders in the USSR Ministry of State Security and entailed pressure on the Church from the party leadership of the regions and republics of the USSR. The ambiguous position of the Council for the Affairs of the Russian Orthodox Church at this moment, expressed in the understanding of a change in the government course in church-state relations and in the absence of directives on this matter, forced the leadership of the Council in the face of G. G. Karpov and Council members to look for new ways of interacting with local authorities. On the one hand, the Council tried to implement the original decisions of the government, and on the other hand, to comply with new realities. The article shows the important and positive role of the Council for the Affairs of the Russian Orthodox Church and personally the Chairman of the Council G. G. Karpov and Council member G. T. Utkin in resolving conflicts between the Church and local bodies of Soviet power in the Saratov region.